Restorative Justice In The Enforcement Of Narcotics Crimes In The Jurisdiction Of The Badung Police - Mahadewi, Kadek Julia; YudhaPradnyana, I Made (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This study was made with the aim of determining the application of restorative justice for narcotics crimes under the jurisdiction of the Badung Police.  Restorative justice is sought so that in the criminal act of narcotics addicts can be optimally recovered, in addition to the high prison occupancy, making law enforcement ineffective for narcotics offenders. The problem raised is how effective is the implementation of restorative justice in the act of narcotics financiers in the jurisdiction of the Badung Police?  This journal uses empirical research, a legal research approach, primary data sources and data collection techniques using interviews and documents.  The results of this study use to measure the effectiveness of this law using 5 factors used, this indicates that Perkap No. 8 of 2021 is still not optimal in handling narcotics crimes in terms of law enforcement factors, sociology of society and legal culture that make it not optimal in implementation.